Pre-Mongolian Medieval Nomadic Monuments from the Saratov Region - Aleksey B. Malyshev; Aleksey I. Rakushin (Нижневолжский археологический вестник)
The purpose of the article is to compile an up-to-date summary of the medieval nomad monuments dating back to the pre-Mongol period on the territory of the Saratov region. The following tasks are solved: cultural and chronological attribution of the complexes; their mapping; generalization and analysis of the data obtained in the context of the history of the Eastern European nomads. Various methods were used in the work: diachronic (periodization of the nomads existence in the studied territory), historical-systemic (study of nomadic society as a system) and historical-comparative (identification of general developmental patterns of nomadic societies), typological (typology and classification of the archaeological materials and complexes), and chronological (study of gradual development of the nomadic culture in the Lower Volga region). The main source of the study is the materials and publications on the nomadic archaeological sites from the Saratov region, as well as previous generalizing works on this topic. Data on 74 monuments are analyzed and mapped. The complexes are grouped into three natural and geographical zones (the basin of the Khopyor and Medveditsa rivers; the Volga Upland; and the Steppe Trans-Volga region). The complexes are also classified according to the three conditional chronological horizons: Saltovo-Mayaki (8th – 9th centuries); Oghuz-Pechenegs (9th – 11th centuries); and Polovtsian (late 11th –early 13th centuries). An attempt is made to correlate the well-known complexes of the Saltovo-Mayaki culture with its separate ethno-cultural groups (the Bulgars, the Khazars, and the Alans) and among the materials of the 9th –11th centuries to single out the Pecheneg and Oghuz components. The Polovtsian sculptures and the burials were correlated with written data on the groups of nomads from the Volga-Don steppes dating back to the middle of the 9th – early 13th centuries.